2015
DOI: 10.1155/2015/507151
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Heparin and Its Derivatives: A Systematic Review

Abstract: Background. Heparin, used clinically as an anticoagulant, also has anti-inflammatory properties. The purpose of this systematic review was to provide a comprehensive review regarding the efficacy and safety of heparin and its derivatives as anti-inflammatory agents. Methods. We searched the following databases up to March 2012: Pub Med, Scopus, Web of Science, Ovid, Elsevier, and Google Scholar using combination of Mesh terms. Randomized Clinical Trials (RCTs) and trials with quasi-experimental design in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
223
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(239 citation statements)
references
References 74 publications
1
223
0
15
Order By: Relevance
“…A recent systematic review with meta-analysis showed the beneficial effects of heparin treatment in asthmatic patients [13]. In normal subjects, heparin can inhibit reactive oxygen species (ROS) generation [14], supporting the observed cardiovascular protective effects, and also increases nitric oxide bioavailability through the release of vessel immobilized myeloperoxidase [15].…”
Section: Anti-inflammatory Cardiovascular and Tissue Protection Actimentioning
confidence: 93%
See 2 more Smart Citations
“…A recent systematic review with meta-analysis showed the beneficial effects of heparin treatment in asthmatic patients [13]. In normal subjects, heparin can inhibit reactive oxygen species (ROS) generation [14], supporting the observed cardiovascular protective effects, and also increases nitric oxide bioavailability through the release of vessel immobilized myeloperoxidase [15].…”
Section: Anti-inflammatory Cardiovascular and Tissue Protection Actimentioning
confidence: 93%
“…As recently reviewed [78] in other clinical trials there was no statistical difference in the primary outcome, showing a narrow spectrum of experimental activity compared to heparin. In another recent review with meta-analysis, heparin and derivatives showed positive effects in cataract surgery [13]. LMWHs compared with heparin, showed more benefit as nephro-and neuroprotective agents.…”
Section: Other Investigated Activities Of Lmwhsmentioning
confidence: 98%
See 1 more Smart Citation
“…Current guidelines recommend an initial treatment with Low Molecular Weight Heparins (LMWHs) [35]. These are useful for their additional properties, such as anti-angiogenic effect [36], anti-inflammatory and immunomodulatory properties [37][38][39]. Practically, if diagnosed within 15 days, LWMH must be administered for two first weeks.…”
Section: Treatmentmentioning
confidence: 99%
“…Toda znižanje vnetnih kazalcev v petih dneh po nastopu akutne VT bi lahko bilo tudi posledica vpliva heparina, s katerim so bolnike zdravili. Poskusi so namreč dokazali, da ima heparin protivnetno delovanje (33).…”
Section: Vnetje In Venska Tromboembolična Bolezenunclassified